2019
DOI: 10.1103/physrevb.100.214518
|View full text |Cite
|
Sign up to set email alerts
|

Extreme sensitivity of the vortex state in a -MoGe films to radio-frequency electromagnetic perturbation

Abstract: Recently, detailed real space imaging using scanning tunneling spectroscopy of the vortex lattice in a weakly pinned a-MoGe thin film revealed that the vortex lattice melts in two steps with temperature or magnetic field, going first from a vortex solid to a hexatic vortex fluid and then from a hexatic vortex fluid to an isotropic vortex liquid. In this paper, we show that the resistance in the hexatic vortex fluid state is extremely sensitive to radio-frequency electromagnetic perturbation. In the presence of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Additionally, the thermal blackbody-radiation has been found to contribute significantly to the performance of superconducting quantum circuits 98 A reminder of the importance of the sensitivity to environmental radiation for materialsresearch was shown in recent experiments by Tamir et al 10 , which showed it in the resistive transition of a:InO, but also of a crystalline 2D superconductor, H2-NbSe 2 . A similar dependence was found recently by Dutta et al 11 in the onset of resistance in the vortex state of a-MoGe-films. It is a reminder that experiments on 'weak' superconductors, on the verge of quantum breakdown, need to be carried out in an electromagnetically wellshielded cryogenic environment, common for mesoscopic research but not typical for materials research.…”
Section: Mesoscopic Approach To Inhomogeneous Superconducting Matsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, the thermal blackbody-radiation has been found to contribute significantly to the performance of superconducting quantum circuits 98 A reminder of the importance of the sensitivity to environmental radiation for materialsresearch was shown in recent experiments by Tamir et al 10 , which showed it in the resistive transition of a:InO, but also of a crystalline 2D superconductor, H2-NbSe 2 . A similar dependence was found recently by Dutta et al 11 in the onset of resistance in the vortex state of a-MoGe-films. It is a reminder that experiments on 'weak' superconductors, on the verge of quantum breakdown, need to be carried out in an electromagnetically wellshielded cryogenic environment, common for mesoscopic research but not typical for materials research.…”
Section: Mesoscopic Approach To Inhomogeneous Superconducting Matsupporting
confidence: 89%
“…• The experimentally observed high sensitivity 10,11 to radio-wave interference, as known for Josephsonjunctions of SIS and SNS-type 73 , calls for an analysis of the effect of microwaves on the study of superconducting materials, which are expected to be spatially inhomogeneous. Both the common Josephson-response due to a local voltage difference, affecting the local phase-differences, should be considered as well as the non-equilibrium effects, which change the Josephson-coupling.…”
Section: Open Problems and Conclusionmentioning
confidence: 99%
“…In a recent preprint [89], some evidence of hexatic and isotropic quantum vortex fluids was reported in extremely weakly pinned a-MoGe superconductor films at very low temperatures, see however [90]. We believe that it is worth searching experimentally for the quantum vortex supersolid phase in that system.…”
Section: Discussion and Outlookmentioning
confidence: 95%
“…By increasing T further, free disclinations form and a fully isotropic liquid is established. This melting sequence has indeed been detected by scanning-tunneling-spectroscopy (STS) imaging of vortices in 2D superconductors [6][7][8][9], but the morphology of dislocations in real systems may be more complicated and depend on microscopic details [1,2]. For example, an STS study of W-based SC films reported a coexistence of liquid with hexatic, as well as with smectic-like (striped) regions of vortex arrangements, and suggested that this might be a feature of melting of 2D solids formed by linearlike units, including vortices in Abrikosov lattices [6].…”
mentioning
confidence: 82%
“…The presence of competing orders may give rise to metastable states and the associated slow dynamics in many systems [11]. An STS study on amorphous MoGe (a-MoGe) thin films did observe [9] a strong suppression of the vortex diffusivity in the presence of hexatic correlations compared to the isotropic liquid, but the nature of the dynamics near the melting transition and its effect on electrical transport have not been explored. Another open question is the evolution of transport properties with H in the presence of orientational correlations.…”
mentioning
confidence: 99%